Androgenetic alopecia as a cardiovascular risk factor - Aneta Wernicka; Maciej Wyzgał; Anna Waśkiel-Burnat; Mariusz Sikora (Termedia Publishing House, 2019)
Androgenetic alopecia is the most common cause of chronic hair loss. The first reports indicating the relationship between androgenetic alopecia and cardiovascular diseases were published in the 1970s. Epidemiological studies confirmed a more frequent occurrence of ischaemic heart disease, development of atherosclerosis and an increased risk of cardiovascular death in this group of patients. Metabolic syndrome and the presence of its components: arterial hypertension, dyslipidemia, insulin resistance and visceral obesity are more frequent in androgenetic alopecia. The pathomechanism of co-occurring androgenetic alopecia and cardiovascular diseases includes several factors such as genetic (increased sensitivity to androgens and activity of 5α-reductase), hormonal (increased concentration of insulin, aldosterone, leptin) and inflammatory (cytokines, free oxygen radicals). Androgenetic alopecia, especially when it begins before the age of 30, has been identified as an independent cardiovascular risk factor. Women and men with pattern hair loss should be closely monitored for other risk factors to start prophylaxis.